Analysis of Employee Engagement and Employee Performance In the Automotive Industry - Dian Nur Mastuti; M Yusuf Sanny; Yuntina, Lily; Jarot Santosa; Moch Nabiel Makariem (Greenation Publisher & Yayasan Global Research National, 2024)
This article analyzing employee engagement and employee performance in the automotive industry within the scope of human resource management science. This article aims to create hypotheses regarding the relationship between factors, which can then be used for further research in the field of human resource management. The research method used in this research is descriptive qualitative. The data used in this research comes from previous research which is still relevant to the current investigation. Data was collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The results of this literature research include: 1) Organization culture influences employee engagement in the automotive industry; 2) Training influences employee engagement in the automotive industry; 3) Work stress influences employee engagement in the automotive industry; 4) Employee assessment influences employee engagement in the automotive industry; 5) Organization culture influences employee performance in the automotive industry; 6) Training influences employee performance in the automotive industry; 7) Work stress influences employee performance in the automotive industry; 8) Employee assessment influences employee performance in the automotive industry; and 9) Employee engagement influences employee performance in the automotive industry.